PRUDENTIAL BANKING PRINCIPLES CONCEPTION IN BANK PICK UP SERVICE CASH SERVICE AGREEMENT IN AN EFFORT TO PROTECT CUSTOMERS BASED ON LEGAL CERTAINTY - I Made Aditya Mantara Putra; I Nyoman Putu Budiartha; Johannes Ibrahim Kosasih (Journal Equity of Law and Governance, 2024)
In the modern world, the role of banking in the economic progress of a country is very large. Almost all sectors related to various financial activities must always require bank services. One of the services offered by the bank is the cash pick up service. In practice, this cash pick up service not only provides convenience to customers, but can be used by certain individuals to commit crimes. This study aims to find solutions and solutions to the vagueness of norms in Article 20A of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector Jo. Law Number 10 of 1998 concerning Banking as well as seeking legal certainty and providing comprehensive protection for the parties involved. The formulation of the problems raised are: 1. What is the philosophical basis for regulating customer transactions in cash pick up service by banks in positive law in Indonesia?; 2. What is the concept of customer protection in transactions through cash pick up service based on the bank's prudential principle as a manifestation of legal certainty?; 3. What is the pickup service cash agreement model that accommodates the bank's prudential principles in an effort to reduce risk and provide protection for parties based on legal certainty in the future? The research method used is normative legal research with the type of statutory approach, conceptual approach, case approach and philosophical approach. The results showed that the philosophical basis for regulating customer transactions in cash pick up service by banks is based on trust, bank prudential principles, and legal certainty. The concept of protection for customers in transactions through cash pick up service reflects the concepts of bank prudence, fairness, transparency, privacy, complaint resolution, trust and legal certainty. A cash pick up service agreement model that accommodates the bank's prudential principles in an effort to reduce risk through the formulation of clauses containing the principles of prudence, risk management, force majeure, legal certainty, cash service specifications, operational provisions, responsibilities, dispute resolution, cash ownership, confidentiality, duration, and closing.